Some remarks concerning Church's Thesis and Hilbert's Axiom - Olszewski, Adam (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
Some facts concerning Church's Thesis are first reminded, then Hilbert's Axiom of Thought is formulated. Hilbert proposed this axiom in 1905. He believed that it belongs to a domain of knowledge that is prior with respect to mathematics. An attempt is made to apply this axiom to some considerations concerning Church's Thesis